2011
DOI: 10.1590/s1982-56762011000100001
|View full text |Cite
|
Sign up to set email alerts
|

Thymol and carvacrol: biotransformation and antifungal activity against the plant pathogenic fungi Colletotrichum acutatum and Botryodiplodia theobromae

Abstract: Fungal growth in fruits may cause spoilage and result in a reduction of their quality and quantity. The aim of the current study was to investigate the antifungal activity and the metabolism of thymol and carvacrol by Colletotrichum acutatum and Botryodiplodia theobromae. The results showed that both compounds provided relatively good control against these plant pathogenic fungi. Mycelial growth of C. acutatum and B. theobromae was inhibited at 50 µg/mL and above. At 150 µg/mL, thymol and carvacrol inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 23 publications
5
54
0
8
Order By: Relevance
“…Accordingly, thyme and clove oils inhibited the growth of P. digitatum and P. italicum completely when added to culture medium at 600 μL L −1 , or by using their volatiles at 24 μL per 8 cm-diameter Petri dish (Yahyazadeh et al, 2009). In addition, the antifungal effect of thymol was higher than that of carvacrol, according to previous reports using Colleotrichum acutatum (Numpaque et al, 2011). An earlier report revealed that other essential oils, apart from thymus and clove oil, such as oregano and cinnamon essential oils, completely inhibited P. digitatum and P. italicum when added to the medium at 1 mL L −1 (Plaza et al, 2004).…”
Section: In Vitro Experimentssupporting
confidence: 73%
“…Accordingly, thyme and clove oils inhibited the growth of P. digitatum and P. italicum completely when added to culture medium at 600 μL L −1 , or by using their volatiles at 24 μL per 8 cm-diameter Petri dish (Yahyazadeh et al, 2009). In addition, the antifungal effect of thymol was higher than that of carvacrol, according to previous reports using Colleotrichum acutatum (Numpaque et al, 2011). An earlier report revealed that other essential oils, apart from thymus and clove oil, such as oregano and cinnamon essential oils, completely inhibited P. digitatum and P. italicum when added to the medium at 1 mL L −1 (Plaza et al, 2004).…”
Section: In Vitro Experimentssupporting
confidence: 73%
“…25 The hydrophobic nature of carvacrol and thymol interact with the lipid bilayer of cytoplasmic membranes cause loss of integrity and leakage of cellular material such as ions, ATP and nucleic acid. 26 Generally, the derivatization of hydroxylated monoterpenes results in enhancement of larvicidal activity against Aedes aegypti of newly obtained compounds, because the presence of hydroxyl groups on their parent structures results in decreased potency, preventing substance penetration in the larva cuticle, [27][28][29][30][31] although this may also result in a decreased activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, some plant pathogens, such as C. acutatum and C. gloeosporioides possess resistant strains to carbendazim (Zhang and Huang, 2007). Meanwhile, thymol has been recognized for its potent antifungal activity (Numpaque et al, 2011).…”
Section: Resultsmentioning
confidence: 99%